Development of The Stem of Jatropha multifida Linn as A New Antimalarial through Erythrocytes Test on Mus musculus Infected by Plasmodium berghei - Agus Sundaryono; Aceng Ruyani; Rika Partika Sari (Faculty of Medicine, Diponegoro University, 2015)
Introduction : Jatropha multifida Linne is known as Betadin plant by the Bengkulunese. The stem extract of J. multifida has antibacterial activity. This study examined the potential of stem extract of J. multifida to be developed as an anti-malarial drugs through trials in M. musculus whose erythrocytes infected by Plasmodium berghei.Methods : Phytochemical test of the stem of J. multifida to test the flavonoids, alkaloids, tannins, saponins, terpenoids and steroids. The stem extract of J. multifida obtained by maceration with 96% ethanol. 30 M. musculus divided 6 groups, each consist of 5 animals. P0 is the negative control groups that were not infected by P berghei. P1 is the positive control groups that were only infected by P berghei, P2 is a comparison groups that were infected with P berghei and chloroquine, groups P3, P4, and P5 were infected by P berghei and treated with stem extract of J multifida with consecutive doses 0.028 g / kgbw, 0.056 g / kgbw and 0.084 g / kgbw. After 24 hours, the number of erythrocytes was observed with hemocytometer then was counted the number of uninfected erythrocytes by P berghei using a microscope at 1000x magnification.Results : The stem extract of J. multifida at doses of 0.028 g/kgbw, 0.056 g/kgbw and a dose of 0.084 g/kgbw were able to increase the number of uninfected erythrocytes by P berghei in M. musculus, respectively an average of 9.135million cell eritrosit/mm3, 7.618 millioncell eritrosit/mm3, and 9.856 millioncell eritrosit/mm3. The ability of stem extract of J. multifida in increasing the number of erythrocytes uninfected with P berghei was much higher than the malaria drug chloroquine diposphat. On one way ANOVA analysis of Fcount ( 13,2 ) > Ftable (2.76 ) , with (α = 0.05), there are noticeable differences in the provision of treatment. The increasing number of uninfected erythrocytes by P berghei was due to the content of flavanol glycosides in J multifida stem. Flavanol glycosides was expected to form Flvanolglycosides-heme complex that could inhibit the formation of P berghei parasites HemazoinConclusion : The stem extract of J. multifida could be developed as a potential anti-malarial drugs since it could increase the number of uninfected erythrocytes by P berghei in M. musculus. Its ability was much higher than the malaria drug chloroquine diposphat